Analisis Pesan Dakwah pada Media Sosial Podcast Login Habib Ja’far dan Onad - Sya'bani, Muhammad Hilmi; Razzaq, Abdur; Hamandia, Muhammad Randicha (Pubmedia Social Sciences and Humanities, 2024)
Islamic Da'wah is often carried out to spread Islamic knowledge, namely the process of inviting or persuading someone to consciously accept and adhere to a religion in order to awaken and restore a person's innate potential. and live a happy life in this world and the hereafter. The purpose of this research is to determine the da'wah message and communication strategy in the Habib Ja'far and Onad login podcast in the social interaction "Strengthen the Faith Podcast Full of Pitfalls". This research uses descriptive qualitative methods, collecting data through observation, interviews and documentation. The results of the research show that: (1) The preaching message in Habib Ja'far and Onad's login podcast in the social interaction "Strengthen the Faith Podcast is Full of Pitfalls" is divided into three aspects: moral message, sharia message, and faith message. First, the moral message found concerns the value of tolerance as a form of learning about differences. Second, the sharia message about the value of patience, especially in the form of learning the differences in fasting. Fasting becomes a barrier that breaks down the walls of tolerance, mutual trust, mutual understanding and mutual respect. Third, the message of faith in the #LogIndiCloseTheDoor podcast seems to be about the value of tolerance in the form of recognizing differences, especially religious differences. Different religions may have different tastes and sensitivities but religious beliefs should not be a problem and (2) Habib Husein Ja'far Al-Hadar's preaching communication strategy in the #LogIndiCloseTheDoor and Onad podcast is preaching using media, preaching using humor, adapting material da'wah with mad'u needs, preaching using correct words, preaching with direct, effective and clear words, preaching with good, polite and not harsh words, preaching using a simple appearance, preaching using attractive titles, and preaching discuss interesting topics.